Using a Private Operator to Establish a Corporatized Public Water Utility : The Management Contract for Johannesburg Water - World Bank (Washington, DC, 2012)
In post-apartheid Johannesburg, South Africa, the city water authority had fallen into disarray (a common situation with urban services). In 2001, a Public-Private Partnership (PPP) emerged as a way to bring new expertise and efficiency to the delivery of public utility services, where a five-year management contract successfully restored services, built local capacity, and helped put Johannesburg Water on a solid footing. The management contract for water supply and sanitation services in Johannesburg, South Africa presents an entirely different perspective. The municipal government implemented the PPP as an interim measure, part of a program specifically designed to improve the efficiency of municipal public services. While an experienced international operator was brought in, the aim of the PPP was not to transfer management to a private concessionaire for the long run. Instead, the goal was to establish a viable, corporatized public water utility by leveraging the expertise of an experienced private operator for a number of years.